Trouble on the frontier: Dutch-Brooke relations and Iban rebellion in the West Borneo borderlands (1841-1886) - Wadley, R.L. (2001)
The colonization of the island of Borneo by the European led to the division between British and Dutch spheres of influence and control. It has had profound consequences for the people that fell under either. Territorial boundaries sliced across well-established networks of communications, trade, common traditions, and strong kinship. From the colonial perspective, boundaries were designed to function negatively, to restrict what was deemed illegal such as smuggling and migration, and positively, to promote legitimate activities like taxation and road construction. Yet the people so partitioned routinely defied the border divisions, causing no small amount of worry to the colonial states. This article examines Dutch-Brooke relations relating to the partitioned Iban population and their efforts to suppress Iban rebellion along the frontier. It first outlines the early phase of competition between the Dutch and James Brooke, leading up to Dutch contact with the Iban settled on their side in the border. The focus then shifts to Dutch and Brooke efforts to suppress headhunting and extend their influence over the border Iban. These efforts culminated in the Kedang Expedition of 1886, a large punitive attack on Iban living on both sides of the border. This expedition and its aftermath provide rich material for examining the difference between the Dutch and Brookes in their administration and attitudes toward the frontier and territorial boundaries.